2021
DOI: 10.20945/2359-3997000000331
|View full text |Cite
|
Sign up to set email alerts
|

Association between fractures and traditional risk factors for osteoporosis and low bone mineral density in patients with obesity

Abstract: Objective: To evaluate the reasons for request of bone mineral density (BMD) evaluation and correlate the BMD results with previous fractures, risk factors for osteoporosis, and clinical characteristics in patients with obesity. Subjects and methods: Cross-sectional, retrospective, single-site study including adult patients with body mass index (BMI) ≥ 30 kg/m 2 and BMD evaluation between January 2015 and May 2016 selected from a BMD database. Data on demographic characteristics, lifestyle habits, comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
(39 reference statements)
0
0
0
1
Order By: Relevance
“…BMI and WC are two internationally accepted parameters for identifying obesity, and numerous earlier studies have found positive connections between BMI, WC, and BMD (11, 30). After adjusting for other factors, researchers discovered that BMI was positively linked with lumbar spine BMD in a study involving 2,218 adults between the ages of 40 and 59 (10). In a study involving 2,903 individuals aged 50 and above, researchers found a positive correlation between BMI and WC and femoral neck BMD, with BMI saturation values of 24.3 kg/m 2 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMI and WC are two internationally accepted parameters for identifying obesity, and numerous earlier studies have found positive connections between BMI, WC, and BMD (11, 30). After adjusting for other factors, researchers discovered that BMI was positively linked with lumbar spine BMD in a study involving 2,218 adults between the ages of 40 and 59 (10). In a study involving 2,903 individuals aged 50 and above, researchers found a positive correlation between BMI and WC and femoral neck BMD, with BMI saturation values of 24.3 kg/m 2 (31).…”
Section: Discussionmentioning
confidence: 99%
“…According to data, obesity incidence in America has climbed from 30.5% in 1999 to 41.9% in 2020, and the yearly medical expenditure associated with obesity is predicted to be at least $173 billion by 2025 (9). Although it was once widely accepted that obesity was positively correlated with either bone density or bone mass (10,11), current research has revealed that the relationship might be the opposite (12,13). Body mass index (BMI) is a typical measurement of obesity, although BMI only assesses overall obesity and ignores how body fat is distributed.…”
Section: Introductionmentioning
confidence: 99%
“…O trabalho realizado por Sampaio et al (2021), um estudo retrospectivo transversal, buscou a relação entre a baixa densidade mineral óssea (DMO) em pacientes obesos e fraturas e fatores de risco para osteoporose, encontrou também associação de baixa DMO e uso de IBPs em pacientes com fraturas prévias (p<0,05). Embora saiba-se que o aumento do índice de massa corporal (IMC) tem influência positiva na DMO, o estudo abordou em contrapartida que o excesso de peso e gordura visceral podem contribuir para o aumento do risco de fraturas em razão da inflamação e da reabsorção óssea.…”
Section: Inibidores De Bomba De Prótons E Obesidadeunclassified